Reduced mortality in former elite endurance athletes - Ruiz, J. R.; Fiuza-Luces, C.; Garatachea, N.; Lucia, A. (International Journal of Sports Physiology and Performance, 2014)
For centuries, the general consensus has been that vigorous, competitive exercise was harmful and shortened life expectancy. Recent data from prospective cohort studies conducted on marathon runners, professional cyclists, and Olympic athletes indicate, however, that regular intense endurance-exercise training has protective benefits against cardiovascular disease and premature death. There are still important questions to be answered, such as what is the optimal dose, in terms of both duration and intensity of training or competition, beyond which the health benefits of regular exercise stabilize or might even potentially disappear.